Ribonucleotide Reduction in Pseudomonas Species: Simultaneous Presence of Active Enzymes from Different Classes - Jordan, Albert (American Society for Microbiology, 1999)
Three separate classes of ribonucleotide reductases exist in nature. They differ widely in protein structure. Class I enzymes are found in aerobic bacteria and eukaryotes; class II enzymes are found in aerobic and anaerobic bacteria; class III enzymes are found in strict and facultative anaerobic bacteria. Usually, but not always, one organism contains only one or two (in facultative anaerobes) classes. Surprisingly, the genomic sequence of Pseudomonas aeruginosa contains sequences for each of the three classes. Here, we show by DNA hybridization that other species of Pseudomonas also contain the genes for three classes. Extracts from P. aeruginosa and P. stutzeri grown aerobically or microaerobically contain active class I and II enzymes, whereas we could not demonstrate class III activity. Unexpectedly, class I activity increased greatly during microaerobic conditions. The enzymes were separated, and the large proteins of the class I enzymes were obtained in close to homogeneous form. The catalytic properties of all enzymes are similar to those of other bacterial reductases. However, the Pseudomonas class I reductases required the continuous presence of oxygen during catalysis, unlike the corresponding Escherichia coli enzyme but similar to the mouse enzyme. In similarity searches, the amino acid sequence of the class I enzyme of P. aeruginosa was more related to that of eukaryotes than to that of E. coli or other proteobacteria, with the large protein showing 42% identity to that of the mouse, suggesting the possibility of a horizontal transfer of the gene. The results raise many questions concerning the physiological function and evolution of the three classes in Pseudomonas species.